ELECTRONIC PAYMENT SAFETY PROVIDE OPTIONS - Elksne, Maija; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
The aim of the reports is to view and compare the electronic payment safety providers. Report consist of three chapters. In the first chapter is witten general information of electronic payments safety. In the second chapter is described security certificate provaider examples and in the third chapter is payment system comparative analysis.